Madrasah Principal Management Strategy in Development Competencies of State High School Teachers in the District Selayar Islands - Tesar Arwandi; Misykat Malik Ibrahim; Mardhiah Hasan (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to: 1) analyze the managerial strategies of madrasah principals in planning teacher competency development, 2) explore the implementation of these strategies, and 3) identify supporting and inhibiting factors. This study uses a qualitative approach with a phenomenological method, with data collection techniques through interviews, observation, and documentation. The study was conducted at MAN Kepulauan Selayar, involving madrasah principals, teachers, and related parties. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The study results indicate that madrasah principals play a strategic role in developing teacher competency through three main strategies: conducting training and workshops, supervising and monitoring performance, and providing motivation and rewards. Madrasah principals send teachers to attend external training organized by the Ministry of Religious Affairs and universities. Supervision is carried out periodically to ensure the implementation of training outcomes, while rewards are given to increase teacher motivation. Supporting factors include the commitment of madrasah principals and teachers, partnerships with external institutions, and support from the school community. However, this study also found inhibiting factors, such as budget constraints, time constraints, remote geographic locations, and limited access to technology and training.